2021
DOI: 10.4102/phcfm.v13i1.2906
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and its impact on glycaemic control in diabetic patients attending Jabulani Dumani community health centre, Gauteng province, South Africa

Abstract: Background: To the best of our knowledge no studies have been conducted to assess the relationship between food insecurity and poor glycaemic control in diabetic patients in peri-urban settings of the South African context.Aim: The study aimed to assess food insecurity and its relationships with glycaemic control and other patient characteristics amongst diabetic patients attending Jabulani Dumani Community Health Centre.Setting: The study was conducted in a primary healthcare facility in the south sub-distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is worth noting that the strategic plans and policies for long-term care and selfmanagement in South Africa are predominated by the self-responsibility of chronic disease patients, and adequate support from primary health care teams to teach and empower patients for appropriate disease self-management [30]. However, the country continues to experience a high number of patients presenting at primary health care (PHC) facilities with poorly controlled T2DM [31] seeking chronic care for related complications mostly entailing lower limb amputations and loss of sight, yet researchers have proven beyond doubt that normal glycaemic control is crucial to prevent diabetes consequences in South Africa [24,32,33]. These consequences have substantial effects on quality of life regarding the increasing medical and rehabilitative costs that come with hospitalisation, medication, and outpatient visits, combined with a loss of income due to the inability to work, among other issues [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the strategic plans and policies for long-term care and selfmanagement in South Africa are predominated by the self-responsibility of chronic disease patients, and adequate support from primary health care teams to teach and empower patients for appropriate disease self-management [30]. However, the country continues to experience a high number of patients presenting at primary health care (PHC) facilities with poorly controlled T2DM [31] seeking chronic care for related complications mostly entailing lower limb amputations and loss of sight, yet researchers have proven beyond doubt that normal glycaemic control is crucial to prevent diabetes consequences in South Africa [24,32,33]. These consequences have substantial effects on quality of life regarding the increasing medical and rehabilitative costs that come with hospitalisation, medication, and outpatient visits, combined with a loss of income due to the inability to work, among other issues [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that the high cost of diabetesfriendly foods such as bulgur wheat and green plantain was reported as a major barrier for diet adherence (Adler et al, 2021). Nsimbo et al (2021) also examined food insecurity and its relationship with glycemic control in people living with diabetes in South Africa. They found that participants with poor glycemic control were 5.38 times more likely to have experienced food insecurity compared to participants who had good glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…(41) In contrast, severe food insecurity showed an association with diabetes in Angola, a characteristic feature of the double burden in developing countries. (42,43) Food insecurity among the lower socio-economic populations exposed them to low-cost processed foods that are likely to increase the risk of NCDs. Developing countries face the dual challenge of addressing food insecurity and promoting healthy diets to prevent NCD risks among various economic subgroups in the population.…”
Section: Journalscambridgeorg/jnsmentioning
confidence: 99%